Measurement of Ozone at Maitri, Antarctica - TIWARI, V. S. (MAUSAM, 1999)
Regular ozone profile measurement over Antarctica has been made by India Meteorological Department since 1987 at Dakshin Gangotri and later at Maitri (70.7°S, 11.7°E) since 1990 with the help of Indian electro-chemical ozone sonde. Surface ozone measurement was also started at Dakshin Gangotri since 1989 and later at Maitri. Ozone sonde data at Dakshin Gangotri and Maitri have been analysed and ozone hole structure has been studied in detail. The drastic decrease in ozone amount is clearly seen between 100 hPa to 30 hPa layer reaching near zero value. Incidently this is the layer where highest ozone concentration occurs during other months except September-October. The ozone hole has been quite severe during 1994-95 with increase in area and depth. During 1996 the Antarctic ozone hole was also similar to previous years. An interesting feature of the 1995 event was the persistence of ozone hole through November & December. Stratospheric temperature changes during 1995 also support that the cold core vortex during 1995 was very cold and persisted up to November.